Linkage analysis and association mapping for plant height in maize - Lima, Rodrigo Oliveira de (2014)
Plant height is one of the most studied traits in maize. It is related to grain yield, planting density and lodging resistance. Several quantitative trait loci associated with plant height have been found through linkage mapping and association mapping in maize. Nevertheless, plant height has not been yet phenotypically and genetically dissected to its components (i.e. internode length and node number) and its genetic architecture remains unknown. Thus, the objective of this study was to explore the phenotypic and genetic architecture of plant height in maize by linkage analysis and association mapping in four RILs populations and in a diverse association panel of maize inbred lines. We evaluated ten maize plant-related traits in 962 recombinant inbred lines derived from four populations and 400 inbred lines from Wisconsin Diverse population (WiDiv). The WiDiv population was genotyped with 458,151 single nucleotide polymorphism (SNP) discovered through RNA-sequencing of maize seedlings. The IBM, OW and NyH RILs populations were genotyped with 8,224, 5,696 and 5,320 SNP using the genotyping-by- sequencing methodology. The NAM22 was genotyped with 1200 SNPs using the panel of 1,536 SNPs by Illumina. Maize plant height-related traits can be phenotypically into ear height, node number, average internode length, and flowering time traits. Plant height showed strong correlation with almost all traits. Node number, below ear node number and flowering time traits were strongly correlated to each other. Maize plant height can be genetically dissected by linkage analysis and association mapping. Several QTL were associated with plant height-related traits, and some QTL hot spots were identified for plant height, ear height and node number. Single nucleotide polymorphism, located in the gene model GRMZM2G171622, was associated with six traits. The candidate genes GRMZM2G108798 and GRMZM2G012766 which were identified in WiDiv population panel were associated with plant height-related traits in our study. These results suggest that ear height, node number, below ear node number, below ear average internode length, and flowering time are the main contributors to maize plant height.